Nest habitat selection by the Austral parakeet in north-western Patagonia - Diaz, Soledad (2013)
Identifying habitat or nesting microhabitat variables associated with high levels of nest success is important to understand nest site preferences and bird–habitat relationships. Little is known about cavity availability and nest site requirements of cavity nesters in southern hemisphere temperate forests, although nest site limitation is suggested. Here we ask which characteristics are selected by the Austral parakeet (Enicognathus ferrugineus) for nesting in Araucaria araucana–Nothofagus pumilio forest in Argentine Patagonia.We compared nest plot and tree characteristics with unused plots and trees among areas of different A. araucana–N. pumilio density. We also examine whether nest plot and tree use and selection, and the associated consequences for fitness of Austral parakeets are spatially related to forest composition. Austral parakeets showed selectivity for nests at different spatial scales, consistently choosing isolated live and large trees with particular nest features in a non-random way from available cavities. Mixed A. araucana–N. pumilio forests are ideal habitat for the Austral parakeets of northern Patagonia, offering numerous potential cavities, mainly in N. pumilio.We argue that Austral parakeet reproduction and fitness is currently very unlikely to be limited by cavity availability, although this situation may be rapidly changing. Natural and human disturbances are modifying south temperate forests with even-aged mid-successional stands replacing old growth forests. Cavity nesting species use and need old growth forests, due to the abundance of cavities in large trees and the abundance of larvae in old wood. Neither of the latter resources is sufficiently abundant in mid-successional forests, increasing the vulnerability and threatening the survival of the Austral.